Changes of soil CO2 flux under different stocking rates during spring-thaw period in a northern desert steppe, China. (December 2015) - Tang, Shiming; Zhang, Yujuan; Guo, Yupin; Zhai, Xiajie; Wilkes, Andreas; Han, Guodong; Jiang, Yuanyuan; Liu, Kesi; Zhou, Pei; Wang, Kun; Wang, Chengjie
Abstract: Atmospheric carbon dioxide (CO2 ) plays an important role in the radiative balance of the earth's atmosphere. Most studies have primarily focused on the growing season. However, few reports are available on CO2 emissions in the Inner Mongolian desert steppe ecosystem during the spring thaw period. To assess the responses of soil-atmosphere CO2 exchange to different stocking rates in the desert steppe, we conducted this study during the winter–spring transition period. The experiment was conducted with four treatments defined along a grazing gradient of un-grazing (UG), light grazing (LG), moderate grazing (MG) and heavy grazing (HG) with three replications of each treatment in the desert steppe of Inner Mongolia during the spring thaw period in 2010 and 2011. Soil CO2 fluxes were measured using Picarro G1301 (an automatic cavity ring-down spectrophotometer) in twelve grazing areas. Our results indicate that mean CO2 emission during the spring thaw period was 8.23 mg CO2 –C m −2 h −1 . Average CO2 fluxes over the two years during the spring thaw period were 10.59 mg CO2 –C m −2 h −1 (UG), 8.10 mg CO2 –C m −2 h −1 (LG), 7.89 mg CO2 –C m −2 h −1 (MG) and 6.35 mg CO2 –C m −2 h −1 (HG). Cumulative CO2 emission amounted to 118.51 kg C ha −1 during the spring thaw period (March–April) on average over two years. In this study, grazing practice significantly reduced CO2 emission during the spring thaw period in the desert steppe. Our results are in accordance with other findings suggesting that emissions of CO2 are regulated significantly by soil temperature during the spring thaw period in this area. The significant empirical relationships provide a simple way to estimate regional amounts of CO2 emission from desert steppe during the spring thaw period. Highlights: CO2 emission by the freezing-thaw period could not be ignored in an annual inventory. Grazing decreased soil CO2 flux during spring-thaw period in desert steppe. Soil CO2 emissions were mainly driven by stocking rate and soil temperature.